PENYULUHAN DAN PENDAMPINGAN TEKNIS PENGELOLAAN DOKUMENTASI ELEKTRONIK HUKUM PADA PERGURUAN TINGGI DI WILAYAH DKI JAKARTA - Sugeng; Nainggolan, Indra L; Zainab, Nina; Syahruddin, Erwin; Romasindah Aidy, Widya (Abdi Bhara, 2024)
This article discusses a community service program focused on the management of legal libraries and documentation in higher education institutions within the DKI Jakarta area. The program aims to enhance the quality of legal library services by optimizing information and legal documentation management systems based on technology. This initiative is driven by the importance of legal libraries as resource centers that support education, research, and the development of legal studies.  The methods employed include training in modern library management, digitization of legal collections, and the implementation of legal reference management software. The program also involves improving the skills of librarians and administrative staff in systematically managing and organizing legal collections. Furthermore, the activities introduce the integration of digital legal information systems to facilitate access and data retrieval for students, lecturers, and researchers.  The results of this program show significant improvements in the effectiveness and efficiency of legal library management. Partner institutions in the program experienced benefits such as easier access to legal literature, more structured documentation systems, and enhanced librarian skills in managing legal data.